2006
DOI: 10.1017/s0952523806231080
|View full text |Cite
|
Sign up to set email alerts
|

Long-term ERG analysis in the partially light-damaged mouse retina reveals regressive and compensatory changes

Abstract: Most of the blinding retinopathies are due to progressive photoreceptor degeneration. Treatment paradigms that are currently being investigated include strategies to either halt or slow down photoreceptor cell loss, or to replace useful vision with retinal prosthesis. However, more information is required on the pathophysiological changes of the diseased retina, in particular the inner retina, that occur as a consequence of photoreceptor cell loss. Here we wished to use light damage as a stoppable insult to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 24 publications
2
18
0
Order By: Relevance
“…In fact, the increase in b-wave/a-wave amplitude implies that the inner retina increased its sensitivity in response to a loss of input from photoreceptors. Similar sensitivity increase in the inner retina has been observed in mild-to-intermediate level photoreceptor degenerations induced by bright light exposure in mice and rats 4143 . The increase in inner retina sensitivity might result from synaptic strengthening between the remaining photoreceptors and inner retinal cells 42 .…”
Section: Discussionsupporting
confidence: 76%
“…In fact, the increase in b-wave/a-wave amplitude implies that the inner retina increased its sensitivity in response to a loss of input from photoreceptors. Similar sensitivity increase in the inner retina has been observed in mild-to-intermediate level photoreceptor degenerations induced by bright light exposure in mice and rats 4143 . The increase in inner retina sensitivity might result from synaptic strengthening between the remaining photoreceptors and inner retinal cells 42 .…”
Section: Discussionsupporting
confidence: 76%
“…29 Given sufficient time for the retina to stabilize, the ERG waves will recover. 30 However, the possibility that the small reduction in photoreceptor activity prior to light damage could blunt the sensitivity of the photoreceptors to light damage requires consideration. Hao et al 25 have shown that the kinetics by which bleached rhodopsin is regenerated, and thus how much pigment is available for bleaching at any given time, dictates the cell's sensitivity to light-induced photoreceptor degeneration.…”
Section: Alternative Pathway Activation In Photoreceptor Degenerationmentioning
confidence: 99%
“…In mice, color vision is mediated by cone photoreceptors, which comprises about 3-5% of cells in the outer nuclear layer [19].…”
Section: Discussionmentioning
confidence: 99%
“…ERG recordings were performed as described previously [19]. In short, mice were dark adapted overnight.…”
Section: Electroretinography (Erg)mentioning
confidence: 99%